Economic Token Techniques as an Effort to Increase the Independence of Children Aged 4-5 Years - Murniyati, Betty; Wardhani, Junita Dwi (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2022)
Early childhood is a very appropriate age to practice independence, because this is a very important aspect for every early childhood. In training aspects of child independence must be carried out regularly, continuously and continuously and in accordance with the age of the child. Providing stimulation and habituation regularly and directed , will make the child more independent faster . The behavior modification method with economic tokens is one of the methods that has been researched and proven to be effective to be applied to increase the independence of early childhood . This study aims to increase the independence of group A kindergarten children in Tamansari 02 Village, Kerjo District, Karanganyar Regency by using economic tokens . The research method used was a quasi-experimental design with one group pre-test post-test. The data collection technique uses a check list instrument totaling 16 items. The subjects of this study amounted to 7 child . The data analysis that the researcher used was the paired sample t test method . From the results of the study it was found that there was a significant difference between the pre-test and post-test independence scores after the child was given treatment p 0.05 (p = 0.000). From these data it has been proven that the application of economic tokens is effective and can increase the independence of group A kindergarten children in Tamansari 02 Village, Kerjo District, Karanganyar Regency.